A systematic review of in vivo stretching regimens on inflammation and its relevance to translational yoga research - Dennis Muñoz-Vergara; Weronika Grabowska; Gloria Y. Yeh; Sat Bir Khalsa; Kristin L. Schreiber; Christene A. Huang; Ann Marie Zavacki; Peter M. Wayne (PLoS ONE, 2022)
Objective To conduct a systematic review evaluating the impact of stretching on inflammation and its resolution using in vivo rodent models. Findings are evaluated for their potential to inform the design of clinical yoga studies to assess the impact of yogic stretching on inflammation and health. Methods Studies were identified using four databases. Eligible publications included English original peer-reviewed articles between 1900–May 2020. Studies included those investigating the effect of different stretching techniques administered to a whole rodent model and evaluating at least one inflammatory outcome. Studies stretching the musculoskeletal and integumentary systems were considered. Two reviewers removed duplicates, screened abstracts, conducted full-text reviews, and assessed methodological quality. Results Of 766 studies identified, 25 were included for synthesis. Seven (28%) studies had a high risk of bias in 3 out of 10 criteria. Experimental stretching protocols resulted in a continuum of inflammatory responses with therapeutic and injurious effects, which varied with a combination of three stretching parameters––duration, frequency, and intensity. Relative to injurious stretching, therapeutic stretching featured longer-term stretching protocols. Evidence of pro- and mixed-inflammatory effects of stretching was found in 16 muscle studies. Evidence of pro-, anti-, and mixed-inflammatory effects was found in nine longer-term stretching studies of the integumentary system. Conclusion Despite the overall high quality of these summarized studies, evaluation of stretching protocols paralleling yogic stretching is limited. Both injurious and therapeutic stretching induce aspects of inflammatory responses that varied among the different stretching protocols. Inflammatory markers, such as cytokines, are potential outcomes to consider in clinical yoga studies. Future translational research evaluating therapeutic benefits should consider in vitro studies, active vs. passive stretching, shorter-term vs. longer-term interventions, systemic vs. local effects of stretching, animal models resembling human anatomy, control and estimation of non-specific stresses, development of in vivo self-stretching paradigms targeting myofascial tissues, and in vivo models accounting for gross musculoskeletal posture.